The Name of the State of Maine: An Irish Perspective. (1st September 2013) - Coates, Richard
Abstract : The three current theories of the origin of the name of the American state of Maine are reviewed and rejected. The connection of the colonist Sir Ferdinando Gorges with Ireland is explored, and a possible origin is proposed in the circumstances of the Anglo-Irish wars of 1594-1603 and their impact on his thoughts and motives.